Children's Legal Protection from Violence (Bullying) In the Education System - Sukmayanti, Made Sinthia (LEGAL BRIEF, 2024)
Currently, there is a lot of aggressive and pressing behavior, either in the form of direct physical action and/or verbal attacks or so-called bullying, occurring in the educational environment from the most basic to the tertiary level, necessitating legal protection efforts for children who are victims of bullying. This study was conducted to determine and assess how legal protection children as victims are bullied under the Child Protection Law. This study employs normative research approaches, using both a statutory and conceptual approach. The results of this study indicate that children have a right to protection from bullying. Article 80 and Article 76C of the Child Protection Law stipulate that sexual offenses and iolence committed by educators, education professionals, fellow students, and/or other parties are prohibited in educational units and will result in punishments